Assessing Drought Hazard and Risk : Principles and Implementation Guidance - World Bank (World Bank, Washington, DC, 2020)
Urban areas in drought-prone regions face serious water shortages affecting its citizens, businesses, and industries. The greater frequency of droughts and more erratic nature of rains in many countries, combined with underlying economic, social, and environmental vulnerabilities, result in increasing impacts to at-risk populations. A first and indispensable step toward adapting to drought is to undertake a drought risk assessment and disclose knowledge that focuses both on specific sectors and users as well on the overall economy. A drought risk assessment is a formal step toward identifying vulnerabilities and taking mitigative and adaptive actions to reduce risk. Drought hazard and risk assessments are often established for the current climate situation; these assessments make use of historical datasets of drought hazards, drought impacts, and information about exposure and vulnerability to drought. This document provides guidelines for assessing drought hazard as well as short- and long-term risks to specific sectors and a country’s overall economy. This document consists of two main sections. Chapter one gives introduction. Chapter two presents basis for the drought guidance. Chapter three describes the key principles of drought hazard and risk assessments; chapter four consists of an implementation guideline for drought risk assessment, providing a step-by-step overview of all activities that need to be done in order to carry out a thorough assessment of drought hazard and or risk. Finally, chapter five presents three examples of the application of the guidelines.